Impact of reflections on the divertor and first wall temperature measurements from the ITER infrared imaging system. (August 2017) - Aumeunier, M.-H.; Kočan, M.; Reichle, R.; Gauthier, E.
Highlights: Photonic transport issue in fully metallic fusion devices. Modeling of ITER Infrared Imaging system based on Monte Carlo ray tracing code. Evaluation of infrared reflections and surface temperature measurement. Abstract: Infrared (IR) images from the equatorial ITER wide angle viewing system are modeled for baseline plasma equilibrium, taking into account the low emissivity, the multiple reflections within the metallic vessel. To do so, a new modeling tool which couples photonic simulations with 3D field line tracing and thermal calculations has been developed. The effects of the parasitic reflections on the surface temperature measurement, Tsurf, on the divertor and first wall are investigated for two kinds of surface roughness (diffuse and specular). The contribution of reflected flux on the whole IR image is evaluated higher than 75% leading to an overestimation of Tsurf by 100% on first wall. For a peak temperature to 800 °C on outer vertical target, unknown emissivity leads to an underestimation of Tsurf by 40% (500 °C), with a risk to not detect a hot spot. Reflections cause an overestimation of Tsurf up to 85% in the colder private region which will impact the measurement of the divertor heat flux profile width.